Autism and Asperger syndrome - Frith, Uta 1941- (Cambridge University Press, 1991)
Is Asperger syndrome a syndrome in its own right or is it a form of autism? Sufferers from the syndrome are like autistic individuals in that they show the same kind of impairments from early childhood; yet they are unlike them in being far more verbally articulate and socially adapted. They can be highly intelligent and reminiscent of eccentrics with their unusual interests, special skills and unworldliness. In this volume several of the major experts in the field discuss the diagnostic criteria of the syndrome, named after Hans Asperger who first described the condition in the 1940s, and illustrate their views with case studies drawn from their clinical practice. They also provide surprisingly practical suggestions on the education and management of autistic children. Current opinion on Asperger syndrome and its relationship to autism is fraught with disagreement and hampered by ignorance. This book gives the first coherent account of Asperger syndrome as a distinct variant of autism